Faktor-faktor Penyebab Kurangnya Motivasi Belajar pada Mata Pelajaran Fiqih di Era Revolusi Industri 4.0 pada Siswa Kelas VIII MTs Yaspen Muslim Pematang Tengah - Aefdi Rahmat; Hayatun Sabariah (STIKes Ibnu Sina Ajibarang, 2024)
Motivation is one of the most important elements in the success of a learning process. However, in the era of the industrial revolution 4.0, the motivation of students has decreased due to several factors. Therefore, the researcher is interested in examining the factors causing the lack of learning motivation of Grade VIII students in the Fiqh subject in the industrial era 4.0. The research method is using a type of field research in the form of a descriptive qualitative approach. The data collection technique is by observation and interview techniques. The results obtained from this study are that there are three main factors causing the lack of motivation of students, including: 1) the absence of learning media, 2) the lack of facilities and infrastructure to support the learning process, 3) the use of monotonous learning methods.